Pedagogika 2050 = Pedagogy 2050 - Chutorański, Maksymilian (Zielona Góra: Lubuskie Towarzystwo Naukowe)
This is an essay on pedagogy of SF (speculative facts / future / feminism).The text consists of two parts. In the first part, I deal with the issues of understanding the future through pedagogical science fiction. In the second one, which is an exercise in the pedagogical imagination, I present excerpts from an unwritten textbook for students of the mid-21st century, in which I show possible problems of the theory and educational research of the future.
Keywords: pedagogika SF; przyszłość; teoria; badania edukacyjne; SF pedagogy; future; theory; educational research